Under pressure: trade competition from low-wage countries and demand for immigrant labor in Italy - Mauro Caselli; Silvio Traverso (Journal of Population Economics, 2026)
This study examines whether trade competition from low-wage countries (LWCs) influences immigration patterns in an advanced economy. We focus on Italy between 2003 and 2013, a period characterized by rising market pressure from China and Eastern Europe. Using census data on sectoral employment, administrative records on immigrants by nationality, and disaggregated bilateral trade data, we investigate whether heightened import competition acted as a pull factor for migrant workers by exploiting the differential exposure of local labor markets. To identify the exogenous component of these trade shocks, we adopt a shift-share instrumental variable strategy, while disaggregating immigrant data by nationality allows us to control in detail for the role of local networks and for bilateral push and pull factors. Our findings indicate that trade competition from LWCs significantly increased local immigrant shares. Exploring potential mechanisms, we find indirect evidence that firms under competitive pressure sought to cut labor costs by relying on a more flexible, lower-paid workforce, primarily composed of foreign workers.
Keywords: F14; F16; F22; J61; 330; Import competition; International migration; Trade shocks; Italy